Evaluation of abrasion loss of asphaltic concrete subjected to ageing - Osman Dawlad, Abdirizak (2014)
Road pavements like other civil infrastructures have a service life. Asphalt Pavements get aged and become weaker, as well the pavement faces abrasion loss of their particles when a huge traffic volume uses on it. Bitumen plays an important role for the ageing of asphaltic concrete pavement. In previous studies, bitumen aged separately and then it added to the asphalt mixture while in reality bitumen ages within asphalt mixture. In this study, asphalt mixture was aged to simulate the site condition. The penetration grade for the study is Pen 80/100, the samples were prepared and then tested for aging according to AASHTO R 30 for short-term and long-term, and then Samples were tested for Cantabro loss test and Marshal Stability to evaluate both the weight loss of the asphaltic concrete mixtures and their stability. Aged samples were compared to the conventional ones (no aging) to indicate the effect of aging on asphalt mix. The results showed that the aged samples for short term and long-term loss more particles compared to the un-aged samples also their stability decreased with the increase of temperature